In vitro antibacterial activity of a silicone-based endodontic sealer and two conventional sealers - Marcela WAINSTEIN; Renata Dornelles MORGENTAL; Silvana Beltrami Gonçalves WALTRICK; Sílvia Dias OLIVEIRA; Fabiana Vieira VIER-PELISSER; José Antonio Poli FIGUEIREDO; Liviu STEIER; Cauana Oliva TAVARES; Roberta Kochenborger SCARPARO (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The aim of this study was to evaluate whether the modification in the silver component is capable of providing GuttaFlow 2 with antibacterial activity against Enterococcus faecalis compared with epoxy resin-based (AH Plus) and zinc oxide and eugenol-based (Endofill) sealers. The antibacterial activity was evaluated using a reference strain of E. faecalis (ATCC 29212). Freshly mixed sealers were subjected to the agar diffusion test (ADT), while the direct contact test (DCT) was performed after materials setting. ADT results were obtained through measurements, in millimeters, of the inhibition zones promoted by the materials, using a digital caliper. In DCT, values of CFU/mL promoted by the three sealers were compared in three experimental periods (1 min, 1 h, and 24 h). The data were analyzed using Kruskal-Wallis and Dunn post-hoc tests (p < 0.05). In both ADT and DCT, GuttaFlow 2 presented no effect against E. faecalis, while Endofill and AH Plus showed similar inhibition zones. Endofill was the only material capable of reducing bacterial growth in DCT. In conclusion, modifications in the silver particle of GuttaFlow 2 did not result in a sealer with antibacterial effect against E. faecalis.